2019
DOI: 10.1002/app.48130
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and dynamic mechanical properties of polyethylene glycol/quartz composites for phase change materials

Abstract: Polyethylene glycol (PEG)/quartz (denoted as BP/Q) composites have been investigated as candidates of phase change materials (PCMs) due to their thermomechanical properties around the glass transition temperature as well as thermal properties between 30 and 600 C. Quartz (q-SiO 2 ) powders were extracted from local sand in Tanah Laut, Pelaihari, South Kalimantan, Indonesia. The composites were prepared by dispersing q-SiO 2 powders in the PEG matrix followed by the wet mixing process. The thermal properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Therefore, the significant drop at approximately 55–62°C can be attributed to the melting temperature T m of PEG in the composites. According to the literature, T m of PEG is approximately 43–62°C 27–29 . In this range, the PEG polymer chain in our composites undergoes slippage with one another, thereby causing a modulus decrease.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, the significant drop at approximately 55–62°C can be attributed to the melting temperature T m of PEG in the composites. According to the literature, T m of PEG is approximately 43–62°C 27–29 . In this range, the PEG polymer chain in our composites undergoes slippage with one another, thereby causing a modulus decrease.…”
Section: Resultsmentioning
confidence: 81%
“…The modulus of PEG/n‐ZrO 2 in the region is compared with those of other samples for the same matrix, for example, PEG/quartz composites. PEG/quartz, which was also referred to as PEG/silica, had the highest storage modulus among various types of silica fillers and was a PCM candidate 28 . In this study, two types of quartz filler are introduced: nanoquartz and microquartz (the composites are denoted as P/nQ and P/mQ, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…There are necessary for a deep analysis of the compounds analyzed, through DSC, Differential Scanning Calorimetry, that allows the study of those processes in which enthalpic variation occurs, for example determination of specific calories, boiling points and fusion, purity of crystalline compounds, reaction enthalpy and determination of other first and second order transitions. The calorimetry applied to the composite materials is used as a tool to detect the possible changes in the crystallinity and microstructure of the matrix by adding a second component as a reinforcement [23][24]. By measuring the melting temperatures and enthalpy of the compounds, these changes can be analyzed through DSC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The tan delta's higher peak is due to the higher degree of molecule mobilization vice versa. [38] Previous research on neat epoxy and DPF-reinforced epoxy composites has shown the dynamic mechanical behavior of these composites. [13] The neat epoxy composite showed very high tan delta (0.7), and after addition of DPF fiber, the viscoelastic factor decreased (0.32).…”
Section: Damping Factormentioning
confidence: 99%